Principle and practice of hydraulic softening top-cutting and pressure relief technology in weakly cemented strata - Wang, Tao; Xu, Guoyao; Liu, Liyuan; Bai, Chaoqiang; Ye, Weiwei; Sun, Lihui (Frontiers in Earth Science, 2024)
Extremely thick and hard roofs are difficult to break in the mining of a working face, and the large area of the suspended roof easily induces a strong ground pressure or dynamic impact disasters. The roof control of a coal mining face in a mine in western China was taken as a case study. The mineral composition, microstructure, and hydrophysical properties of the hard roof overlying the coal seam were analyzed. The characteristics of the weak-cementation strata that are prone to mud and collapse when encountering water were targeted to investigate the hydraulic softening roof-cutting and pressure relief technology. It was found that the clay mineral composition in the roof plate accounts for 60.6%. After 24 hours of natural immersion, the rock strength decreased by approximately 10.3%-49%, and further immersion caused disintegration. By arranging high and low double-row water injection softening drilling holes in the cutting hole and roadway of the working face, the strength of roof rock strata in the target area was reduced, and the initial weighting step distance and weighting strength of the working face were reduced. The hydraulic softening roof-cutting pressure relief technology effectively regulated the weighting step distance of the hard roof and the peak weighting of the working face.